Sacred scripture and secular struggles - Meconi, David Vincent (Bible in ancient Christianity, 2015)
Preliminary Material -- Introduction /David Vincent Meconi S.J. -- 1 The Fragmentation and Inversion of Empire in the Christian Apocryphal Acts /Nicole Kelley -- 2 “Sic est voluntas Dei”: Latin Patristic Views on 1 Peter 2:13–17 /Jonathan P. Yates -- 3 Power and Tradition in Apostolic Constitutions 7 /Clayton N. Jefford -- 4 Tertullian and Military Service: The Scriptural Arguments in De corona /Geoffrey D. Dunn -- 5 Irenaeus and the Kingdoms of the World /D. Jeffrey Bingham -- 6 The Weak God of the Gospels: Mercy, Mysticism, and Martyrdom in Origen’s Contra Celsum /Roberto J. De La Noval -- 7 Diodore on the Politics of Kingship in Psalm 2 /Benjamin D. Wayman -- 8 Justus sibi lex est: The Donatist Interpretation of the Law in Romans 2:14 /Alden Lee Bass -- 9 Should a Christian Sell Everything? Early Interpretations of the Rich Young Man /Stephen M. Hildebrand -- 10 Abraham, Samson, and ‘Certain Holy Women’: Suicide and Exemplarity in Augustine’s De ciuitate dei 1.26 /Melanie Webb -- 11 From Slave to Friend: John 15, Philemon, and Slavery in Augustine /Joseph E. Capizzi -- 12 From Ordo to Potestas: Romans 13 and Saint Augustine’s Chastened Civil Confidence /David Vincent Meconi -- Bibliograhy -- Index.